The History of Educational Direction in the Republic of Kazakhstan at Half of ХІХ Century and at the Beginning of ХХ Century (Journal of Educational Sciences, 2017)
The article is devoted to the history of the development of education in Kazakhstan in the late 19th and early 20th centuries, the place and role of Jadidism in the formation of a new worldview among the Turkic peoples, the causes of the emergence of new-method teaching, and it was analyzed the activities of Muslim communities and their development. The purpose of the study was to identify important trends in the development of the education system in the late 19th and early 20th centuries.A tendency has been established within the framework of the educational reform of the late XIX – early XX centuries: the implementation of the policy of tsarism in creating schools for the education of children. After the Manifesto of October 17, 1905, with the adoption of freedom of worship, speech, etc., began the opening of schools – madrasahs at mosques. Freedom of religion in Kazakhstan in connection with the opening of sets of madrasahs at mosques led to the flourishing of Muslim customs.Persecution against the leaders of the liberation movement, and the very activity of the colonial system in Kazakhstan turned into discontent, and led to the strengthening of the role of Islam in society; Islam became the flag of the national liberation struggle.Key words: missionary work, public education, Islam, kadimi, jadidism.